The 24-h urinary cortisol/cortisone ratio for monitoring training in elite swimmers - Atlaoui, D.; Duclos, M.; Gouarne, C.; Lacoste, L.; Barale, F.; Chatard, J. C. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The effect of training variations on 24-h urinary cortisol/cortisone (C/Cn) ratio was investigated in highly trained swimmers to determine whether it could be a good marker of training stress and performance. METHODS: Fourteen swimmers (five female and nine male) were tested after 4 wk of intense training (IT), 3 wk of reduced training (RT), and 5 wk of moderate training (MT). At the end of each period, the swimmers performed in their best event at an official competition. Individual performances were expressed as a percentage of the previous season's best performance. The fatigue state was evaluated with a questionnaire. RESULTS: The C/Cn ratio was statistically different for the three periods (IT: 1.10 +/- 0.7, RT: 0.64 +/- 0.3, and MT: 0.57 +/- 0.2). The differences in the C/Cn ratio between two consecutive performances were related to the differences in performance (r = -0.52, P < 0.01), and the C/Cn ratio was significantly related to the total training (r = 0.32, P < 0.05) and total score of fatigue (TSF) (r = 0.35, P < 0.03) over the follow-up period. Cn levels were related to the dryland training (r = -0.46; P < 0.01) and TSF (r = -0.40; P < 0.02). During IT, variations in the C/Cn ratio were related to the changes in the mean intensity (r = -0.67; P < 0.02) and to TSF (r = 0.69; P < 0.01). CONCLUSION: The 24-h C/Cn ratio was moderately related to both training and performance whereas Cn levels were only related to training. The C/Cn ratio could be a useful indicator for monitoring the overreaching state in elite swimmers.